Hard carbon material, preparation method thereof and battery
By forming a stable carbon cladding layer on the surface of the hard carbon core, the side reactions and inefficiency problems caused by surface defects in the battery are solved, and higher first-time Coulomb efficiency and cyclic stability are achieved.
Patent Information
- Application Number
- CN202510020863.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-25
AI Technical Summary
During the battery operation, hard carbon materials have many side reactions due to the many defect sites on the surface during the battery operation. The first time, the Coulomb efficiency is low, and the surface SEI film is uneven and stable, which affects the battery circulation performance.
By forming a stable carbon coating layer on the surface of the hard carbon core, the particle size D50 is 5 to 18 μm and the thickness of the carbon coating layer is 0.3 to 4 μm. Hard carbon materials are prepared by solid phase mixing and thermal coating treatment.
The surface defects of hard carbon materials are reduced, the surface morphology is improved, the specific surface area is reduced, the first discharge side reaction is reduced, and the first Coulomb efficiency and cycle stability are improved.
Smart Images

Figure CN119890262A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of battery materials, and more specifically, relates to a hard carbon material and a preparation method thereof, and a battery. Background Art
[0002] Hard carbon is a commonly used negative electrode material in sodium ion batteries. It has good conductivity and a large number of disordered defects and vacancies in its structure, which provide more active sites for sodium storage and doping modification sites for impurity elements. It has a large interlayer spacing and can show good structural stability during the sodium ion extraction process. As the negative electrode of sodium ion batteries, hard carbon has the advantages of suitable working voltage and high specific capacity. In addition, hard carbon has a wide range of sources, and renewable biomass, resin or asphalt can all be used as the carbon source of hard carbon. The preparation process is simple, low cost, and suitable for large-scale production.
[0003] However, the presence of many defect sites on its surface will lead to more side reactions during the operation of the battery, resulting in low initial coulombic efficiency and uneven and unstable surface SEI film, which will affect the battery cycle performance to a certain extent. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present application is to provide a hard carbon material and a preparation method and a battery, aiming to improve the surface stability and cycle performance of the hard carbon material.
[0005] An embodiment of the present application is implemented by providing a hard carbon material, which includes a hard carbon core and a carbon coating layer, wherein the carbon coating layer at least partially coats the surface of the hard carbon core; wherein the particle size D50 of the hard carbon material is 5 to 18 μm, and the thickness of the carbon coating layer is 0.3 to 4 μm.
[0006] In some embodiments, the particle size D01 of the hard carbon material is ≥1 μm; and / or, among the particles of the hard carbon material, the volume proportion of particles with a particle size less than 2 μm is less than 2%; and / or, the surface oxygen content of the hard carbon material is 0.5% to 12%; and / or, the carbon content of the hard carbon material is 89% to 97%; and / or, the carbon content of the hard carbon core is 90% to 98%; and / or, the material of the carbon coating layer is amorphous carbon.
[0007] In some embodiments, the particle size D01 of the hard carbon material is ≥2 μm; and / or the amorphous carbon includes soft carbon, hard carbon or a combination thereof; and / or the Raman spectrum Id / Ig of the carbon coating layer is in the range of 1.02 to 1.20; and / or the specific surface area of the hard carbon material is 0.5 to 4 m 2 / g; and / or, the compacted density of the hard carbon material is 0.92 to 1.15 g / cm 3
[0008] Correspondingly, the present application also provides a method for preparing a hard carbon material, comprising: providing a pre-carbonized material and a coating source, solid-phase mixing the pre-carbonized material and the coating source to obtain a pre-coated precursor; performing a heat coating treatment on the pre-coated precursor to obtain a hard carbon precursor; wherein the atmosphere of the heat coating treatment is an inert atmosphere or an oxygen-containing atmosphere; and performing high-temperature carbonization on the hard carbon precursor to obtain a hard carbon material.
[0009] In some embodiments, before providing the pre-carbonized material and the coating source, the method further includes: providing a carbon source and pre-carbonizing the carbon source to obtain the pre-carbonized material.
[0010] In some embodiments, the carbon source includes one or more of asphalt, resin or biomass; wherein the asphalt is selected from petroleum asphalt or coal tar; the resin includes one or more of phenolic resin, polyester resin, epoxy resin, polyformaldehyde resin, urea-formaldehyde resin, furfural resin, furfural ketone resin, acrylic resin, polyamide, polyimide, polyvinyl alcohol; the biomass includes one or more of coconut shell, lotus leaf stalk, straw, starch, esterified starch; and / or the pre-carbonization treatment is: treating at 500-700°C in an inert atmosphere for 1-5h.
[0011] In some embodiments, the mass ratio of the coating source to the pre-carbonized material is (2-8):100; and / or the particle size D50 of the pre-carbonized material is 5-14 μm; and / or the particle size D50 of the coating source is 2-10 μm; and / or the ratio of the particle size D50 of the coating source to the particle size D50 of the pre-carbonized material is 0.3-2.0; and / or the solid phase mixing is carried out by a high-speed mixer, the rotation speed of the high-speed mixer is 400 rpm-1000 rpm, and the mixing time is 1 h-4 h.
[0012] In some embodiments, the mass ratio of the coating source to the pre-carbonized material is 5:100; and / or the ratio of the particle size D50 of the coating source to the particle size D50 of the pre-carbonized material is 0.3 to 1.5.
[0013] In some embodiments, the temperature of the thermal coating treatment is 100-450°C; and / or, the time of the thermal coating treatment is 1-8 hours; and / or, the inert atmosphere is a vacuum atmosphere, or an atmosphere formed by one or more of nitrogen, helium, neon, argon, krypton, xenon, and radon; and / or, the oxygen-containing atmosphere is pure oxygen, air, or a mixed atmosphere formed by oxygen and an inert atmosphere; and / or, the thermal coating treatment is dynamic thermal coating.
[0014] In some embodiments, the temperature of the high temperature carbonization is 1100-1600° C.; and / or, the time of the high temperature carbonization is 1-3 hours; and / or, the atmosphere of the high temperature carbonization is an inert atmosphere.
[0015] Correspondingly, the present application also provides a battery, comprising the above-mentioned hard carbon material, or comprising the hard carbon material prepared by the above-mentioned preparation method of the hard carbon material.
[0016] The hard carbon material of the present application includes a hard carbon core and a carbon coating layer, wherein the carbon coating layer at least partially coats the surface of the hard carbon core; wherein the particle size D50 of the hard carbon material is 5 to 18 μm, and the thickness of the carbon coating layer is 0.3 to 4 μm. By forming a stable carbon coating layer on the surface of the hard carbon core, the hard carbon material has fewer surface defects, a more regular surface morphology, and a relatively reduced specific surface area; when the hard carbon material with a core-shell structure is used as a negative electrode material in a battery, it can reduce the first discharge side reaction, improve the first coulomb efficiency, and enhance the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a hard carbon material provided in the present application;
[0018] Figures 2 to 5 SEM images of the hard carbon materials corresponding to Example 1, Comparative Example 2, Example 3, and Comparative Example 3, respectively;
[0019] Figure 6 The diagrams of the power-on cycles of Example 1 and Comparative Example 2 are shown;
[0020] Figure 7 The charge and discharge curves of Example 1 and Comparative Example 1 are shown in FIG. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application and are not used to limit the present application. In the present application, unless otherwise stated, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to".
[0022] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0023] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0024] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0025] The present application provides a hard carbon material, the hard carbon material comprising a hard carbon core and a carbon coating layer, wherein the carbon coating layer at least partially covers the surface of the hard carbon core. By forming a stable carbon coating layer on the surface of the hard carbon core, the hard carbon material has fewer surface defects, a more regular surface morphology, and a relatively reduced specific surface area; when the hard carbon material with a core-shell structure is used as a negative electrode material in a battery, it can reduce the first discharge side reaction, improve the first coulomb efficiency, and enhance the cycle stability.
[0026] In one embodiment, in the particle size distribution of the hard carbon material, D50 is 5 to 18 μm, specifically 5 to 7 μm, 7 to 9 μm, 9 to 12 μm, 12 to 15 μm, 15 to 18 μm, etc.
[0027] In one embodiment, the thickness of the carbon coating layer may be 0.3-4 μm, specifically 0.3-0.5 μm, 0.5-1 μm, 1-2 μm, 2-4 μm, etc. Of course, it may also be other values within the above range, which is not limited here.
[0028] Furthermore, the particle size D01 of the hard carbon material is ≥1 μm, and can be specifically 1-1.2 μm, 1.2-1.5 μm, 1.5-2 μm, 2-2.3 μm, 2.3-2.6 μm, 2.6-3 μm, 3-3.5 μm, 3.5-4 μm, 4-4.2 μm, 4.2-4.5 μm, etc. In a specific embodiment, the D01 of the hard carbon material is ≥2 μm. There are very few particles with smaller particle sizes in the hard carbon material particles, which can improve the cycle performance when applied to the battery.
[0029] In one embodiment, among the particles of the hard carbon material, the volume proportion of particles with a particle size of less than 2 μm is less than 2%, and can further be less than or equal to 1.2%, and can specifically be 0% to 0.4%, 0.4% to 0.6%, 0.6% to 1.0%, 1.0% to 1.1%, 1.1% to 1.2%, etc., and of course, it can also be other values within the above range, which are not limited here. In this embodiment, the content of fine particles or powders with smaller particle sizes in the hard carbon material is relatively small.
[0030] The material of the carbon coating layer is amorphous carbon, which may specifically include soft carbon, hard carbon or a combination thereof. In one embodiment, the Raman spectrum Id / Ig of the carbon coating layer is in the range of 1.02 to 1.20.
[0031] In one embodiment, the carbon content of the hard carbon material with a core-shell coating structure is 89% to 97%, specifically 89% to 92%, 92% to 95%, 95% to 97% μm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0032] In one embodiment, the carbon content of the hard carbon core is 90% to 98%, specifically 90% to 92%, 92% to 95%, 95% to 98%, etc. Of course, it can also be other values within the above range, which is not limited here.
[0033] In one embodiment, the surface oxygen content of the hard carbon material is 0.5% to 12%, specifically 0.5% to 1.0%, 1.0% to 4.0%, 4.0% to 7.0%, 5.0% to 6.0%, 7.0% to 12.0%, etc. Of course, it can also be other values within the above range, which is not limited here. In this embodiment, the surface oxygen content is obtained by performing XPS test on the hard carbon material to obtain the C\N\O peak area ratio.
[0034] In one embodiment, the compacted density of the hard carbon material is 0.92-1.15 g / cm 3 , specifically 0.92 to 0.95 g / cm 3 , 0.95~0.97g / cm 3 , 0.97~1.05g / cm3 1.05~1.15g / cm 3 Of course, it can also be other values within the above range, which is not limited here.
[0035] In one embodiment, the specific surface area of the hard carbon material is 0.5 to 4 m 2 / g, specifically 0.5 to 1.0 m 2 / g, 1.0~1.5m 2 / g, 1.5~2.0m 2 / g, 2.0~3.0m 2 / g, 3.0~4.0m 2 / g, etc., and of course, it can also be other values within the above range, which is not limited here.
[0036] The present application provides a method for preparing a hard carbon material. Figure 1 , Figure 1 This is a flow chart of an embodiment of a method for preparing a hard carbon material provided by the present application, comprising the following steps:
[0037] Step S11: providing a pre-carbonized material and a coating source, and mixing the pre-carbonized material and the coating source in a solid phase to obtain a pre-coated precursor;
[0038] Step S12: subjecting the pre-coated precursor to a heat coating treatment to obtain a hard carbon precursor; wherein the atmosphere of the heat coating treatment is an inert atmosphere or an oxygen-containing atmosphere;
[0039] Step S13: carbonizing the hard carbon precursor at high temperature to obtain a hard carbon material.
[0040] In this embodiment, through solid phase mixing and thermal coating treatment, the softened coating source will be coated on the surface of the pre-carbonized carbon source, evenly forming a layer of stable amorphous carbon layer, which can repair the surface defects of the hard carbon material and make the surface morphology more regular. The surface edges and sharp shapes of the hard carbon material obtained after coating are significantly reduced, and the specific surface area is reduced, thereby reducing the first discharge side reaction, improving the first coulomb efficiency, and enhancing the cycle stability.
[0041] Compared with liquid phase coating, the solid phase coating method in this embodiment does not involve the use of solvents and has the advantages of low cost and simple process.
[0042] Conventional solid phase coating generally mixes the selected coating material with the raw material evenly, and then sinter and carbonize to obtain the coated hard carbon. The first disadvantage is that the coating material often has a limited contact area with the raw material. During the high-temperature sintering process, the coating material is pyrolyzed and attached to the surface area of the raw material, which leads to uneven coating; secondly, after sintering, the coating material often adheres to the raw material and agglomerates, which makes depolymerization difficult, and the depolymerization easily causes the coating layer to fall off and the morphology to be irregular. The solid phase coating method of solid phase mixing and heat treatment coating in this embodiment can avoid the uneven problem caused by conventional solid phase coating, achieve uniform coating, regular morphology, and improve the agglomeration phenomenon to a certain extent. The capacity of the balanced material, the first coulomb efficiency, the median voltage, etc. can be regulated by coating.
[0043] In step S11:
[0044] The pre-carbonized material is obtained by pre-carbonizing the carbon source. In one embodiment, before step S11, the step further includes: pre-carbonizing the carbon source to obtain the pre-carbonized material.
[0045] Among them, the carbon source can be asphalt, resin or biomass; among them, asphalt can be petroleum asphalt or coal tar; resin can include one or more of phenolic resin, polyester resin, epoxy resin, polyformaldehyde resin, urea-formaldehyde resin, furfural resin, furfural ketone resin, acrylic resin, polyamide, polyimide, polyvinyl alcohol, etc.; biomass can include one or more of coconut shell, lotus leaf stalk, straw, starch, esterified starch, etc.
[0046] Among them, the esterified starch includes one or more of alkenyl succinate starch, starch acetate, maleate starch, succinate starch, starch xanthate, starch amino acid methyl ester, starch sulfosuccinate, starch sulfate, starch nitrate, starch selenate, and starch phosphate.
[0047] In a specific embodiment, the pre-carbonization treatment is specifically a treatment at 500-700° C. for 1-5 hours in an inert atmosphere. Specifically, the inert atmosphere is a vacuum atmosphere, or an atmosphere formed by one or more of nitrogen, helium, neon, argon, krypton, xenon, and radon.
[0048] In this step, the coating source includes one or more of asphalt, phenolic resin, glucose, citric acid, etc. Specifically, the melting point or softening temperature of the coating source is in the range of 100 to 400°C. Different coating sources will affect the graphitization degree of the coating layer in the final hard carbon material. A higher graphitization degree means a higher order and a softer carbon; a lower graphitization degree means a harder carbon.
[0049] Specifically, the solid phase mixing can be uniformly mixed by a high-speed mixer, the rotation speed of the high-speed mixer can be 400 rpm to 1000 rpm, and the processing time can be 1 hour to 4 hours.
[0050] In one embodiment, the mass ratio of the coating source to the pre-carbonized material is (2-8):100, that is, the coating ratio of the coating source is 2%-8%. Specifically, the mass ratio of the two can be 5-7μm, 7-9μm, 9-12μm, 12-14μm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0051] It is understandable that the carbon source, pre-carbonized material, and coated source may all be subjected to a crushing process to reduce the particles and improve the mixing uniformity. The crushing method may be performed by jet milling or mechanical milling.
[0052] In a specific embodiment, the particle size D50 of the carbon source and the pre-carbonized material can be 5-14 μm, specifically 5-7 μm, 7-9 μm, 9-12 μm, 12-14 μm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0053] In a specific embodiment, the particle size D50 of the coating source can be 2-10 μm, specifically 2-4 μm, 4-6 μm, 6-8 μm, 8-10 μm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0054] Furthermore, in a specific embodiment, the ratio of the particle size D50 of the coating source to the particle size D50 of the carbon source (or the pre-carbonized material) is 0.3-2.0, such as 0.3-1.5, 0.5-0.8, 0.8-1.0, 1.0-1.2, 1.2-1.5, etc.
[0055] The particle size distribution of the pre-coated precursor prepared in this step is basically consistent with the particle size distribution of the carbon source or pre-carbonized material, with a D50 deviation of about ±0.3 μm. In other words, the difference between the particle size D50 of the pre-coated precursor and the particle size D50 of the carbon source or pre-carbonized material is -0.3 to 0.3 μm.
[0056] In step S12:
[0057] In one embodiment, the temperature of the heat coating treatment can be determined according to the melting point or softening temperature of the coating source. Specifically, the temperature of the coating heat treatment is 20-100° C. higher than the melting point or softening temperature of the coating source.
[0058] In one embodiment, the temperature of the heat coating treatment is 100-450°C, specifically 100-200°C, 200-300°C, 300-400°C, 400-450°C, etc., and of course it can also be other values within the above range, which is not limited here. The time of the heat coating treatment is 1-8h, specifically 1-3h, 3-5h, 5-8h, etc., and of course it can also be other values within the above range, which is not limited here.
[0059] In this step, during the heat coating process, the softened coating source will adhere to the fine particles in the mixed particles, resulting in a decrease in the content of fine particles in the hard carbon material, so that D01 in the particle size distribution increases. Specifically, the particle size distribution of the fused coating product (i.e., the hard carbon precursor) obtained after the heat coating process is shifted to the increasing direction compared with the pre-carbonized material as a whole. Specifically, the particle size D01 increases by 0.2 to 2 μm, and D50 increases by about 0.3 to 4 μm.
[0060] The atmosphere of the thermal coating treatment may be an inert gas or an oxygen-containing atmosphere. The inert atmosphere is a vacuum atmosphere, or an atmosphere formed by one or more of nitrogen, helium, neon, argon, krypton, xenon, and radon. The oxygen-containing atmosphere is an atmosphere containing oxygen, such as pure oxygen, air, or a mixed atmosphere formed by oxygen and an inert atmosphere.
[0061] In this step, by adjusting the atmosphere of the heat coating treatment, the oxygen-containing functional groups on the surface of the hard carbon material, the oxygen content and the degree of graphitization of the coating layer therein are regulated, and the capacity and rate performance of the hard carbon material are regulated.
[0062] In a specific embodiment, the coating source is selected from asphalt. When the atmosphere during the hot coating treatment is an inert atmosphere such as nitrogen, the coating layer in the prepared hard carbon material is soft carbon; when the atmosphere during the hot coating treatment is an oxygen-containing atmosphere such as air, the coating layer in the prepared hard carbon material is relatively hard carbon.
[0063] In another embodiment, the coating source is selected from glucose, and the coating layer in the prepared hard carbon material is hard carbon.
[0064] In one embodiment, the heat coating treatment is a dynamic heat coating treatment, that is, the pre-coated precursor is in a heated and continuously moving state during the heat coating treatment. In a specific embodiment, the pre-coated precursor is subjected to a heat coating treatment, specifically: the pre-coated precursor is placed in a fusion stirring and heating device such as a rotary kiln, and the coating fusion treatment is performed in a corresponding atmosphere at a preset temperature and time.
[0065] In step S13:
[0066] The temperature of the high temperature carbonization is 1100-1600°C, specifically 1100-1200°C, 1200-1300°C, 1300-1400°C, 1400-1600°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0067] The high-temperature carbonization time is 1 to 3 hours, specifically 1 to 1.5 hours, 1.5 hours to 2 hours, 2 hours to 2.5 hours, 2 hours to 2.5 hours, 2.5 hours to 3 hours, etc. Of course, it can also be other values within the above range, which is not limited here.
[0068] The atmosphere of the high temperature carbonization is an inert atmosphere. It can be understood that the atmosphere of the pre-carbonization treatment involved in this application is also an inert atmosphere. The inert atmosphere can refer to the relevant description in this application and will not be repeated here.
[0069] In a specific embodiment, the high-temperature carbonization equipment can be one or a combination of a box furnace, a push plate kiln (furnace), a roller kiln (furnace), a tunnel furnace, and a rotary kiln. Dynamic high-temperature carbonization can improve the uniformity of carbonization.
[0070] In some embodiments, before mixing the precarbonized material and the coating source, the precarbonized material is subjected to a vibration screening process, which can improve the fluidity of the precarbonized material, reduce the agglomeration of particles of the precarbonized material, and improve the subsequent processability of the precarbonized material. It should be understood that the present application does not limit the frequency and time of the vibration screening, and those skilled in the art can select a suitable vibration screening frequency and time according to actual experimental conditions (such as a vibration screening instrument, etc.), which are all within the scope of protection of the present application.
[0071] In some other embodiments, before mixing the pre-carbonized material and the coating source, the pre-carbonized material or the carbon source is subjected to vibration screening and demagnetization treatment.
[0072] In a preferred embodiment, the above demagnetization treatment is performed several times, preferably 1 to 5 times. In a specific embodiment of the present application, the magnetic field strength of the above demagnetization treatment is 8000Gs to 10000Gs. Too much magnetic material will cause the self-discharge of the battery. During the charge and discharge process of the battery, it will gradually nucleate and grow with the change of temperature. During the cycle process, it will precipitate to form metal dendrites and pierce the diaphragm. Magnetic materials, as excellent conductors of electrons, will cause the battery to short-circuit and affect the thermal stability of the battery. The above demagnetization treatment of the present application can remove magnetic materials such as iron, cobalt, nickel, zinc, copper and manganese in the pre-carbonized material or carbon source, thereby reducing the content of magnetic materials in the hard carbon material.
[0073] In the present application, by the above-mentioned preparation method of the hard carbon material, the specific surface area of the coated hard carbon material is significantly reduced by 0.5 to 3 m2 compared with the uncoated hard carbon material.2 / g, D50 increases by 0.3-4μm, the first coulombic efficiency increases by 0.5-2%, the capacity increases by 0-20mAh / g, and both the cycle performance and rate performance are improved.
[0074] The present application also provides a battery, which includes a positive electrode and a negative electrode, wherein the negative electrode comprises the hard carbon material provided by the present application. In a specific embodiment, the battery is a sodium ion battery.
[0075] The above technical solutions are described in detail below in conjunction with specific embodiments. It should be understood that these are merely exemplary and are not intended to limit the present application. Materials identical or similar to the types, models, qualities, properties or functions of the following reagents and instruments can be used to implement the present application. The experimental methods used in the following embodiments and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following embodiments and comparative examples, unless otherwise specified, can all be obtained from commercial sources.
[0076] Example 1
[0077] This embodiment provides a bitumen-coated coconut shell-based hard carbon and its preparation, comprising the following steps:
[0078] Step 1: The pre-carbonized material (pre-carbonized coconut shell, D50 is 7.26 μm) and the crushed coating source (asphalt with a softening point of 250°C) are mixed evenly, wherein the coating ratio of asphalt is 5%, that is, the mass ratio of asphalt to pre-carbonized material is 5:100, and the ratio of the coating source particle size D50 to the pre-carbonized material D50 is 0.4;
[0079] Step 2: placing the mixture in step 1 in a rotary kiln at 280°C for 2 hours in an air atmosphere;
[0080] Step 3: Carbonize the product in step 2 at 1200°C for 2 hours to obtain a hard carbon material.
[0081] Example 2
[0082] This embodiment is basically the same as embodiment 1, and the only difference is that the atmosphere in step 1 is changed to N2.
[0083] Example 3
[0084] This embodiment is basically the same as the embodiment 1, except that the pre-carbonized material in step 1 is changed from pre-carbonized coconut shell to pre-carbonized starch material, and the D50 is 13.23 μm.
[0085] Example 4
[0086] This embodiment is basically the same as embodiment 1, except that the coating source in step 1 is changed from asphalt to glucose; and the insulation temperature in step 2 is changed to 160°C.
[0087] Example 5
[0088] This embodiment is basically the same as Embodiment 1, except that the coating ratio of asphalt is 2%.
[0089] Example 6
[0090] This embodiment is basically the same as Embodiment 1, except that the coating ratio of asphalt is 8%.
[0091] Example 7
[0092] This embodiment is basically the same as Embodiment 1, except that the ratio of the coating source particle size D50 to the pre-carbonized material D50 is 0.5.
[0093] Example 8
[0094] This embodiment is basically the same as Embodiment 1, except that the ratio of the particle size of the coating source to the D50 of the pre-carbonized material is 1.5.
[0095] Example 9
[0096] This embodiment is basically the same as Embodiment 1, except that the ratio of the particle size of the coating source to the D50 of the pre-carbonized material is 2.
[0097] Comparative Example 1
[0098] A conventional coating material preparation comprises the following steps:
[0099] Step 1: Mix the pre-carbonized coconut shell and 3% crushed asphalt evenly;
[0100] Step 2: Keep the product of step 1 at 1200°C for 2 hours to obtain hard carbon.
[0101] Comparative Example 2
[0102] This comparative example is basically the same as Example 1, except that steps 1 and 2 are not performed, and the pre-carbonized coconut shell is directly carbonized in step 3 to obtain hard carbon.
[0103] Comparative Example 3
[0104] This comparative example is basically the same as Example 3, except that steps 1 and 2 are not performed, and the starch pre-carbonized material is directly carbonized in step 2 to obtain hard carbon.
[0105] [test]
[0106] The hard carbon materials of Examples 1 and 3 and Comparative Examples 2 and 3 were subjected to scanning electron microscopy (SEM) testing, see Figures 2 to 5 , Figures 2 to 5SEM images of the hard carbon materials corresponding to Example 1, Comparative Example 2, Example 3, and Comparative Example 3, respectively. Figure 2 and Figure 3 It can be seen that after the coconut shell-based hard carbon is coated, the edges and sharp shapes are significantly reduced, and the surface morphology is more regular. Figure 4 and Figure 5 It can be seen that after the starch-based hard carbon is coated, there is an obvious coating layer structure on its surface.
[0107] The hard carbon materials of the examples and comparative examples were tested for particle size, compacted density, specific surface area, carbon content, surface oxygen content, and Raman spectroscopy. The performance of batteries prepared using the hard carbon as negative electrode material was also tested.
[0108] Among them, referring to the particle size distribution laser diffraction method of GB / T 19077-2016, the British Malvern Mastersizer2000E laser particle size analyzer was used to measure and obtain the particle size D01, D50, and the volume percentage of particles with a particle size less than 2μm; the compaction density meter of Yuanneng Technology was used for testing, and the compaction density was measured at 150MPa; the specific surface area was measured by BET; and the surface relative carbon content and oxygen content were measured using XPS.
[0109] Sodium ion secondary battery production:
[0110] The hard carbon material prepared in the above embodiments and comparative examples is made into a slurry with conductive carbon black and a binder, uniformly coated on an aluminum foil and dried to make an electrode, a sodium sheet is used as a counter electrode, a glass fiber film is used as a diaphragm, and a mixed solution of 1 mol / L NaPF6 and ethylene carbonate (EC): dimethyl carbonate (DEC) = 1:1 vol.% is used as an electrolyte to make a button battery.
[0111] The test conditions are as follows: the first discharge test is performed at 20 mA / g to 0.01 V, then charged to 2.5 V, and tested at a constant temperature of 25°C to obtain the charge and discharge capacity and the first coulombic efficiency. The constant current charge and discharge test is performed at 0.1C, the charge and discharge voltage range is 0V-2.5V, and the test is performed at a constant temperature of 25°C. The number of cycles is 100, and the capacity retention rate after 100 cycles is measured.
[0112] The above test results are shown in Table 1 and Table 2. Figure 6 The power-on cycle diagrams of Example 1 and Comparative Example 2 are shown below. Figure 7 The charge and discharge curves of Example 1 and Comparative Example 1 are shown in FIG.
[0113] Table 1:
[0114]
[0115] Table 2:
[0116]
[0117] From Table 1 and Table 2, Figure 6 and Figure 7 It can be seen that:
[0118] Compared with the conventional solid phase coating of Comparative Example 1, the hard carbon material (Examples 1-2 and 4-9) prepared by the preparation method including solid phase coating provided in the present application can be coated with a coating layer of sufficient thickness on the surface, and can reduce the presence of tiny particles in the final hard carbon material, thereby significantly improving the battery capacity and cycle performance.
[0119] Compared with Comparative Example 2 and Comparative Example 3 which are not coated, the hard carbon material with a coating structure (Example 1 and Example 3) of the present application can reduce the specific surface area, reduce the presence of tiny particles with a particle size less than 2 μm, reduce the surface oxygen content, and when applied to the battery, can improve the capacity and first efficiency to a certain extent, and significantly improve the cycle performance.
[0120] It can be understood that in each embodiment and comparative example, the particle size of the final hard carbon material after uncoating treatment and coating treatment can reflect the thickness of the coating layer.
[0121] In summary, the hard carbon material with a coating structure provided in the present application and the method for preparing a hard carbon material including solid-phase thermal coating provided in the present application can reduce surface defects of the hard carbon material, make the surface morphology more regular, and relatively reduce the specific surface area; the hard carbon material with a core-shell structure can reduce the first discharge side reaction when used as a negative electrode material in a battery, improve the first coulombic efficiency, and enhance the cycle stability.
[0122] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A hard carbon material, characterized in that: The hard carbon material comprises a hard carbon core and a carbon coating layer, wherein the carbon coating layer at least partially coats the surface of the hard carbon core; wherein the particle size D50 of the hard carbon material is 5 to 18 μm, and the thickness of the carbon coating layer is 0.3 to 4 μm.
2. The hard carbon material according to claim 1, characterized in that The particle size D01 of the hard carbon material is ≥1 μm; and / or, Among the particles of the hard carbon material, the volume proportion of particles with a particle size of less than 2 μm is less than 2%; and / or, The surface oxygen content of the hard carbon material is 0.5% to 12%; and / or, The carbon content of the hard carbon material is 89% to 97%; and / or, The carbon content of the hard carbon core is 90% to 98%; and / or, The material of the carbon coating layer is amorphous carbon.
3. The hard carbon material according to claim 2, characterized in that The particle size D01 of the hard carbon material is ≥ 2 μm; and / or, The amorphous carbon includes soft carbon, hard carbon or a combination thereof; and / or, The Raman spectrum Id / Ig range of the carbon coating layer is 1.02 to 1.20; and / or, The specific surface area of the hard carbon material is 0.5 to 4 m 2 / g; and / or, The compacted density of the hard carbon material is 0.92 to 1.15 g / cm 3 .
4. A method for preparing a hard carbon material, characterized in that: The steps include: Providing a pre-carbonized material and a coating source, and mixing the pre-carbonized material and the coating source in a solid phase to obtain a pre-coated precursor; The pre-coated precursor is subjected to a heat coating treatment to obtain a hard carbon precursor; wherein the atmosphere of the heat coating treatment is an inert atmosphere or an oxygen-containing atmosphere; The hard carbon precursor is carbonized at high temperature to obtain a hard carbon material.
5. The preparation method according to claim 4, characterized in that: Before providing the pre-carbonized material and the coating source, the method further includes: providing a carbon source and performing a pre-carbonization treatment on the carbon source to obtain the pre-carbonized material.
6. The preparation method according to claim 5, characterized in that: The carbon source includes one or more of asphalt, resin or biomass; wherein the asphalt is selected from petroleum asphalt or coal asphalt; the resin includes one or more of phenolic resin, polyester resin, epoxy resin, polyoxymethylene resin, urea-formaldehyde resin, furfural resin, furfural ketone resin, acrylic resin, polyamide, polyimide, polyvinyl alcohol; the biomass includes one or more of coconut shell, lotus leaf stem, straw, starch, esterified starch; and / or, The pre-carbonization treatment is: treating at 500-700° C. for 1-5 hours in an inert atmosphere.
7. The preparation method according to claim 4, characterized in that: The mass ratio of the coating source to the pre-carbonized material is (2-8):100; and / or, The particle size D50 of the pre-carbonized material is 5 to 14 μm; and / or, The particle size D50 of the coating source is 2 to 10 μm; and / or, The ratio of the particle size D50 of the coating source to the particle size D50 of the pre-carbonized material is 0.3 to 2.0; and / or, The solid phase mixing is carried out by a high-speed mixer, the rotation speed of the high-speed mixer is 400 rpm to 1000 rpm, and the mixing time is 1 hour to 4 hours.
8. The preparation method according to claim 7, characterized in that: The mass ratio of the coating source to the pre-carbonized material is 5:100; and / or, The ratio of the particle size D50 of the coating source to the particle size D50 of the pre-carbonized material is 0.3 to 1.
5.
9. The preparation method according to claim 4, characterized in that: The temperature of the heat cladding treatment is 100 to 450° C.; and / or, The heat coating treatment time is 1 to 8 hours; and / or, The inert atmosphere is a vacuum atmosphere, or an atmosphere formed by one or more of nitrogen, helium, neon, argon, krypton, xenon, and radon; and / or, The oxygen-containing atmosphere is pure oxygen, air, or a mixed atmosphere formed by oxygen and an inert atmosphere; and / or, The heat cladding process is dynamic heat cladding; and / or, The high temperature carbonization temperature is 1100-1600° C.; and / or, The high temperature carbonization time is 1 to 3 hours; and / or, The atmosphere of the high temperature carbonization is an inert atmosphere.
10. A battery, characterized in that: The hard carbon material comprises the hard carbon material according to any one of claims 1 to 3, or the hard carbon material prepared by the method for preparing the hard carbon material according to any one of claims 4 to 9.